2011
DOI: 10.1091/mbc.e10-11-0915
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping kinetochore targets of CK2 and Aurora B kinases in mitotic regulation

Abstract: CK2 associates with kinetochore protein Mif2/CENP-C. Loss of CK2 results in defects in chromosome segregation, short mitotic spindle, and activation of the spindle assembly checkpoint. CK2 phosphorylates Mif2 and Ndc10. CK2 phosphorylation plays antagonistic and synergistic roles with Aurora B phosphorylation of Mif2 and Ndc10, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…Studies have suggested that Ndc10 is a target of both Ipl1 and casein kinase 2 (CK2) (40,41). Phosphorylations of multiple serine and threonine residues influence Ndc10 localization on the anaphase spindle and targeting to kinetochore.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have suggested that Ndc10 is a target of both Ipl1 and casein kinase 2 (CK2) (40,41). Phosphorylations of multiple serine and threonine residues influence Ndc10 localization on the anaphase spindle and targeting to kinetochore.…”
Section: Resultsmentioning
confidence: 99%
“…400 μg of purified proteins was subjected to phosphorylation by Hrr25. Phosphorylated residues of Ede1C (900–1381 aa) were identified by tandem mass spectrometry analysis as previously described (Peng et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a unique feature of CENP-C Mif2 or a CENP-C Mif2 -binding protein is important for the interaction of Mub1/Ubr2 with kinetochore particles. However, despite the close association of Mub1/Ubr2 with CENP-C Mif2 , we did not detect ubiquitylation of CENP-C Mif2 or a CENP-C Mif2 mutant allele ([47] and data not shown). Because we could not detect a stable association of Mub1/Ubr2 with endogenous kinetochores, Mub1/Ubr2 likely bind to kinetochore particles during the purification process.…”
Section: Discussionmentioning
confidence: 57%